The Meaning of Dewi Sri in the Perspective of Spiritual Ecologism in the Indigenous Peoples of Kampung Naga and Kampung Cireundeu - Ulifia, Evi Fita (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2024)
This research explores the cultural significance of Dewi Sri among the indigenous communities of Kampung Naga and Kampung Cireundeu, focusing on the similarities and differences in her essence as well as the relationship between these beliefs and Ecofeminism. Conducted in Tasikmalaya Regency and Cimahi, the study employed an anthropological approach with a comparative method to analyze religious practices and ancestral values. Findings revealed that both communities regard "goah" as a sacred area for storing staple foods, accessible only to women, who perform rituals honoring Dewi Sri with offerings like coconut and golden banana salads. This reflects the values of Spiritual Ecofeminism, emphasizing the interconnectedness of nature, femininity, and spirituality. The research highlights how Dewi Sri symbolizes a spiritual representation of women, serving as a medium for promoting sustainable environmental practices within these communities. Contribution: The research enriches academic discourse by linking indigenous knowledge systems to contemporary Ecofeminist frameworks, thereby fostering a deeper appreciation for the role of cultural heritage in environmental stewardship.